A Structural Overview of Inuktitut - Sammons, Susan (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1993)
AbstractThis structural overview includes a brief discussion of Inuktitut as a polysynthetic agglutinative language. It outlines affiliations with other language families and lists the sub-branches and dialects of the language. The phonological and morphophonemic systems of Inuktitut are described. The central morphology of the language is discussed in two subsections, one dealing with the noun phrase, the other with the verb phrase.